Early monitoring of infliximab serum trough levels predicts long-term therapy failure in patients with axial spondyloarthritis. (4th March 2022) - Martínez-Feito, A; Navarro-Compán, V; Hernández-Breijo, B; Olariaga-Mérida, E; Peiteado, D; Villalba, A; Nuño, L; Monjo, I; Diego, C; Pascual-Salcedo, D; Nozal, P; Balsa, A; et al.
Abstract : Objective: To evaluate whether serum infliximab trough levels (ITL) during the early stages of treatment are predictive of long-term clinical failure in patients with axial spondyloarthritis (axSpA). Methods: Longitudinal observational study involving 81 patients with axSpA monitored during infliximab therapy. Serum ITL were measured before starting infliximab treatment and at weeks 2 (W2), W6 and W12 of treatment. Disease activity was assessed by Ankylosing Spondylitis Disease Activity Score (ASDAS) at baseline, W24 and W52, and every 6 months thereafter until treatment discontinuation, regardless of the reason. Non-clinically important improvement was defined by ΔASDAS<1.1. The association between serum levels during the early stages and clinical outcomes (non-clinically important improvement at W52, drug survival and drop-out due to secondary inefficacy) was investigated through logistic regression models and Kaplan Meier curves. Receiver operating characteristic (ROC) curves were employed to determine the best cut-off for serum ITL. Results: Out of the 81 patients, 45 (56%) did not achieve clinical improvement at W52. These patients had lower serum ITL at W12 compared to those who improved: ITL [median (IQR)]: 4.1(0.9-8.3) µg/mL vs 7.1 (4.3–11.3) µg/mL, respectively;p = 0.007). ITL<6.7 µg/mL at W12 was significantly associated with: i) not achieving clinical improvement at W52 (OR: 2.3; 95%CI: 1.3–3.9); ii) shorter drug survival (5.0 years (95% CI 3.8–6.2) vs 7.0 years (95% CI 4.8–6.9; p = 0.04), and iii) higher drop-out rates due to secondary inefficacy (OR: 3.5; 95% CI: 1.2–10.2). Conclusion: Low serum ITL at W12 were associated with long-term clinical failure in patients with axSpA, due to secondary inefficacy.